2013
DOI: 10.13066/kspm.2013.8.4.513
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Complex Exercise with Abdominal Drawing-in Maneuver on Expiratory Abdominal Muscles Activation and Forced Pulmonary Function for Post Stroke Patients

Abstract: PURPOSE: The purpose of this study was to investigate characteristics of the forced pulmonary function test effect and abdominal muscles activation by combined complex exercise with abdominal drawing-in maneuver training of chronic stroke patients. METHODS: 14 post stroke patients(10 males and 4 females) involved voluntary this study and we divided two groups into CEG(complex exercise group) and CEAG (complex exercise and abdominal drawing-in maneuver group).(n=7, per goup). Each groups implicated the 2 times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…We performed the ADIM training in the prone position with adults with instability that was reported of the thickened core muscle, the transverse abdominis, and obliqus abdominus interni. Another previous study had also reported that the ADIM increases the activity of transverse abdominis and obliqus abdominus interni of the deep abdominal muscles [24].…”
Section: Discussionmentioning
confidence: 72%
“…We performed the ADIM training in the prone position with adults with instability that was reported of the thickened core muscle, the transverse abdominis, and obliqus abdominus interni. Another previous study had also reported that the ADIM increases the activity of transverse abdominis and obliqus abdominus interni of the deep abdominal muscles [24].…”
Section: Discussionmentioning
confidence: 72%
“…Another previous study also shows that the ADIM increases the abdominal deep muscle activity of TrA and ADIM, and that the increased muscle activity is observed in the group applied with ADIM. 18 After a stroke, the ability of a patient to maintain trunk control in sitting and standing positions is a fundamental skill for achieving autonomy in activities of daily living. The trunk control performance of patients soon after a stroke has been found to be closely associated with long-term functional improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were then taught to preferentially activate their TrA by performing the ADIM with visual feedback from the pressure biofeedback unit. 18…”
Section: ) Adimmentioning
confidence: 99%
“…몸통 안정화를 향상시키는 여러 운 동 방법 중 복부 드로우-인 기법은 몸통 안정화에 관련 된 주위 근육들을 활성화시키는 운동방법으로 특히 몸 통 안정화에 중요한 배가로근을 선택적으로 자극시킬 수 있으며, 이미 요통환자들에게 검증되어 최근 뇌졸중 환자들에게 몸통 안정성을 향상시키기 위해 적용하고 있다 [9]. 그러나 뇌졸중 환자들 같은 경우 선택적으로 단일 근육만을 활성화시키면, 주위 근육들의 근 약화를 초래할 수 있어 가장 효율적인 운동 방법이라고 할 수 없어 [10], 이를 보안하기 위해 호흡이나 팔-다리의 움직 임을 병행하여 효율적인 복부 드로우-인 기법을 제시하 고 있는 추세이다 [11] 특히, 호흡은 누구나 쉽고 자연스 럽게 접할 수 있는 운동 방법이며 [12], 호흡 운동은 호흡 근의 근력, 지구력 향상뿐만 아닌 [13], 척추의 안정성을 제공하며, 복부와 요추 주위 근육들에 긍정적인 변화 주는 운동이다 [14].…”
unclassified